A DEFORMATION APPARATUS FOR THREE-DIMENSIONAL COAXIAL DEFORMATION AND ITS APPLICATION TO RHEOLOGICALLY STRATIFIED ANALOGUE MATERIAL - Zulauf G.; Zulauf J.; Hastreiter P.; Tomandl B. (My University, 2003)
A new apparatus is described that supports all types of three-dimensional coaxial deformation from pure constriction to pure flattening. Up to 78% shortening is possible at strain rates ranging from 4x10-6 to 1x10-2s-1. The apparatus has been used to study the influence of the deformation regime on the geometry of a deforming stiff layer embedded in a weak matrix. Layer and matrix consist of plasticine, the apparent viscosity η and stress exponent n of which vary from 2x106 to 2x107Pas and 6-9, respectively. First results suggest a considerable influence of the deformation regime on the geometry of the deformed layer including its thickness. If the viscosity ratio between layer and matrix is small (η2/η1#5), folding is restricted to the flattening and plane strain regime, the latter if the layer is initially oriented perpendicular to the long axis X of the finite strain ellipsoid. If the layer is oriented perpendicular to the intermediate Y axis under plane and constrictional strain, low viscosity ratios result in boudinage, but folding is hardly developed. However, simultaneous growth of folds and boudins is possible under pure constriction at a viscosity ratio of 10. Three-dimensional images, based on computer tomography, suggest a strong interaction between such coeval folds and boudins, resulting in characteristic deformation patterns that should not occur if both structures form in sequence during polyphase deformation.
Keywords: DEFORMATION APPARATUS; THREE-DIMENSIONAL COAXIAL DEFORMATION; RHEOLOGICALLY STRATIFIED ANALOGUE MATERIAL